Bicara itu ada seninya: Perspektif komunikasi dan kebudayaan di UIN Maulana Malik Ibrahim Malang - indi, rovida (Maliki Interdisciplinary Journal, 2025)
Speaking is not merely uttering words but an art that embraces word choice, style, tone, and sociocultural context. This article explores the art of speaking, how verbal communication becomes a medium of expression and identity formation, and how educational and cultural environments at UIN Maulana Malik Ibrahim Malang influence one’s speaking artistry. The research method uses literature review, examining multiple etheses and studies from UIN Malang related to communication, literature, education, and social interaction. The findings indicate that the art of speaking is influenced by literary education, the role of teachers, Islamic culture, and social norms. Therefore, fostering speaking skills as an art should be integrated into curricula, communication training, and environments that support verbal creativity.